Analisis Pengelolaan Fasilitas Homestay di Kampung Buricak Burinong Desa Pakualam Kecamatan Darmaraja - Yayu Cahyudin; Gilang Pratama Putra; Irena Novarlia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research analyzes the management of homestay facilities in Buricak Burinong Village, Pakualam Village, Darmaraja District, West Java. This research aims to provide guidance for homestay managers in managing human resources efficiently and effectively, and provide recommendations for improving the quality of accommodation facilities in Buricak Burinong Village. With this analysis, it is expected to know the supporting and inhibiting factors in homestay management, as well as efforts that can be made to increase tourist attraction and the welfare of local communities through the development of better homestay facilities. The research method uses a qualitative descriptive method by conducting observations and interviews with the parties involved in managing homestay facilities in Buricak Burinong Village. The data analysis method used is SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). The results of the analysis show that the management of Kampung Buricak Burinong homestay facilities is located in quadrant I, so the right way to be applied is the S-O strategy that can be done, namely, increasing online and offline promotions by involving the community and the support of the government. This step aims to increase tourist attractiveness in the management of homestay facilities, comfort, and ease of tourists visiting Buricak Burinong Village homestay.